2013
DOI: 10.1097/prs.0b013e3182865dfb
|View full text |Cite
|
Sign up to set email alerts
|

rhBMP-2 with a Demineralized Bone Matrix Scaffold versus Autologous Iliac Crest Bone Graft for Alveolar Cleft Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 28 publications
3
80
0
11
Order By: Relevance
“…A few studies have examined the efficacy of the use of rhBMP on cleft alveolar bone grafting outcomes. 24,25 These studies have shown rhBMP to be a viable alternative for secondary alveolar cleft repair. However, the long-term effects of these on clinical outcomes and immediate perioperative outcomes are unknown.…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have examined the efficacy of the use of rhBMP on cleft alveolar bone grafting outcomes. 24,25 These studies have shown rhBMP to be a viable alternative for secondary alveolar cleft repair. However, the long-term effects of these on clinical outcomes and immediate perioperative outcomes are unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Compostos como as proteínas morfogené-ticas ósseas (BMP) têm mostrado resultados promissores em diversos estudos, sendo necessário contudo realizar mais estudos, com amostras populacionais maiores e tempos de follow-up mais prolongados. [2][3][4]13,14 Estão descritos na literatura alguns fatores que promovem o sucesso da intervenção, nomeadamente a fase de erupção, o tipo de material enxertado, desenho do retalho cirúrgico e manuseamento dos tecidos durante o enxerto, assim como a experiência do cirurgião responsável. 9,15 Também a adesão ao plano terapêutico e higiene dentária podem constituir um importante fator de sucesso ou falência da intervenção.…”
Section: Discussionunclassified
“…Adicionalmente, al no tener una liberación controlada y prolongada obliga a utilizar mayores dosis para poder obtener una formación ósea adecuada (Carreira et al 2014b). En el año 2013 se realizó un estudio retrospectivo utilizando fichas clínicas por 2 años donde se obtuvieron 55 pacientes con un promedio de edad de 11,8 años y 21 meses de seguimiento (Francis et al, 2013 Tabla I. Publicaciones relativas al uso de rhBMP-2 en matriz de esponja de colágeno en fisuras alveolares.…”
Section: Estructura Molecular Y Actividad Biológicaunclassified
“…Sin embargo se ha descrito que la aplicación de PLGA puro como matriz para la regeneración ósea posee propiedades mecánicas sub-óptimas para poder soportar funciones de carga. Por ésta razón se ha utilizado en combinación con otros materiales como cerámicos o vidrio (Gentile et al, 2014). Porosidad.…”
Section: Uribeunclassified